D1R- and D2R-Medium-Sized Spiny Neurons Diversity: Insights Into Striatal Vulnerability to Huntington’s Disease Mutation - Bergonzoni, Guendalina; Döring, Jessica; Biagioli, Marta (Frontiers in Cellular Neuroscience, 2021)
Huntington’s Disease (HD) is a devastating neurodegenerative disorder caused by an aberrant expansion of the CAG tract within the exon 1 of the HD gene, HTT. HD progressively impairs motor and cognitive capabilities, leading to a total loss of autonomy and ultimate death. Currently, no cure or effective treatment is available to halt the disease. Although the HTT gene is ubiquitously expressed, the striatum appears to be the most susceptible district to the HD mutation with Medium-sized Spiny Neurons (MSNs) (D1R and D2R) representing 95% of the striatal neuronal population. Why are striatal MSNs so vulnerable to the HD mutation? Particularly, why do D1R- and D2R-MSNs display different susceptibility to HD? Here, we highlight significant differences between D1R- and D2R-MSNs subpopulations, such as morphology, electrophysiology, transcriptomic, functionality and localization in the striatum. We discuss possible reasons for their selective degeneration in the context of HD. Our review suggests that a better understanding of cell type-specific gene expression dysregulation within the striatum might reveal new paths to therapeutic intervention or prevention to ameliorate HD patients’ life expectancy.